Notes on the Indo-malayan Species of Geophila Don - Thothathri, K. (Indian Forester, 1963)
The generic name Geophila Don (1825) of Rubiaceae is invalidated by the earlier homonym Geophila Berger (1803), belonging to Liliaceae. W.F. Wight has, therefore, changed the generic name Geophila Don to Carinta (1905). Due to this change new combinations have become necessary for a few Asiatic species and in the present paper 5 new combinations are proposed for the Malaysian species